Genes and genetics - Shoals, James; Smith, Ryan (Growth, development and reproduction of the human body., 2021)
Explores the history of human thought about heredity from ancient times, when people knew children resembled their parents but could not say why, to today's modern discoveries of genes and genetic transference. Includes a glossary.